Trade War Shocks and Volatility Spillovers between Fossil Fuel Markets and Biofuel Feedstocks: Empirical Evidence from the U.S.–China Trade Dispute - Avazkhodjaev, Salokhiddin; Dhiensiri, Nont; Rakhimov, Eshmurod; Shayusupova, Lobar; Turaeva, Adiba (International Journal of Energy Economics and Policy, 2025)
Volatility dynamics in fossil fuel and agricultural commodity markets are shaped by a complex interplay of geopolitical, macroeconomic, and policy shocks. This article examines volatility transmission and cross-market linkages between crude oil and major biofuel feedstock commodities — soybean, corn, canola, and sunflower — from 2016 to 2025. Using a VAR–GARCH–BEKK framework and volatility impulse response analysis, the study provides evidence on how disruptive events such as the U.S.–China trade war, Brexit, OPEC supply interventions, the COVID-19 pandemic, and renewed trade tensions influence variance and covariance across integrated energy–commodity systems. The results show that volatility transmission is a persistent structural feature, with shocks in the oil sector rapidly propagating into biofuel feedstocks through input-cost, substitution, and policy channels. Volatility shocks are asymmetric, with negative shocks — particularly trade disputes and geopolitical conflicts — exerting stronger effects than positive ones. Volatility impacts are also commodity-specific: soybean exhibits the greatest sensitivity due to its dual role in biofuel production and trade, while corn and sunflower respond more strongly to demand-side disturbances. Several exogenous shocks beyond the 2018 trade war generate volatility effects equal to or greater than its impact, highlighting the multidimensional drivers of systemic risk. These findings deepen understanding of cross-market dynamics in integrated commodity systems and underscore the need for coordinated policies, targeted stabilization tools, and forward- looking strategies incorporating climate transition risks and predictive analytics to enhance market resilience and safeguard food and energy security in an increasingly uncertain global environment.